PATRIOTIC ATTITUDES OF HIGH SCHOOL STUDENTS: THE CASE OF ANKARA PROVINCE KAZAN - Mehmet ELBAN (Fırat University, 2019)
Territorial modern national states were emerged along with citizenship in the nineteenth century and patriotism had been the main component of citizenship. Thus, all nation states included patriotism in the school curriculum to inculcate patriotic attitudes to students. Initially, nation states aimed to inculcate strong patriotism to its citizens. However, today it is intended that attitudes of students to be a democratic as well as inculcating patriotism. In this context, the purpose of this study is to investigate attitudes of the 11th grade students’ patriotic and blind attitudes.Sample of the study was chosen randomly from the pool of 3 secondary schools in Kazan district of Ankara province as 3 schools in the academic year of 2009-2010. Totally 240 students, 131 female and 109 male from 11th grades of these 3 schools participated to the study. In order to gather data, Patriotic Attitudes Scale were used as measurement instrument. The datas obtained from the research was analyzed by using the computer program,‘’ SPSS (Statistical Package for Social Sciences) for Windows 13’’ For the analysis of the data, t test, Mann Whitney U test, Kruskal Wallis and one-way ANOVA was used. Significance level is .05 for all the analyses.The results revealed that the students in this study group have high level constructive and medium level blind patriotic attitudes. On the other hand gender differences were found in terms of neither constructive patriotic attitudes nor blind patriotic attitudes. However according to school type variable, there is a significant difference among students’ constructive patriotic attitudes.